Efektivitas Penyaluran Zakat di Indonesia: Pendekatan Rasio Keuangan dan Sharia Enterprise Theory - Novendi Arkham Mubtadi; rohmad abidin; Qurrota Ayun (JIEF : Journal of Islamic Economics and Finance, 2021)
The purpose of this study is to determine the level of effectiveness of zakat distribution in Indonesia with the financial ratio approach and Sharia Enterprise Theory. This study uses a combination of qualitative and quantitative methods. The object used in this research is the financial statements of 41 Zakat Institutions in the post-positive Zakat Core Principles (ZCP). This study uses financial ratio analysis, namely the activity ratio. The results of calculating the Allocation to Collection Ratio (ACR) in 41 Zakat Institutions in Indonesia show that the Zakat Institutions is very effective in distributing the collected zakat funds. In connection with the Sharia Enterprise Theory, the results indicate that the Zakat Institutions has implemented the concept of hablumminallah and hablumminannas which explains that zakat funds are asnaf rights so that all zakat funds collected must be channeled optimally. Besides that, mustahiq will certainly feel more satisfied when their rights are channeled in the right time.